Impact of time to surgery after neoadjuvant chemotherapy in operable breast cancer patients. Issue 4 (April 2017) - Omarini, C.; Guaitoli, G.; Noventa, S.; Andreotti, A.; Gambini, A.; Palma, E.; Papi, S.; Tazzioli, G.; Balduzzi, S.; Dominici, M.; Cascinu, S.; Piacentini, F.
Abstract: Background: The optimal time interval between the end of neoadjuvant systemic therapy (NST) and breast surgery is still unclear. It is not known if a delay in surgery might influence the benefit of primary chemotherapy. The aim of this study is to evaluate the relationship between time to surgery (TTS) and survival outcomes. Patients and methods: According to TTS, women with diagnosis of BC treated with NST were divided into two cohorts: group A = 21 days or fewer and group B = longer than 21 days. OS and RFS were estimated and compared according to TTS and known prognostic factors. Results: A total of 319 patients were included in the study: 61 in group A and 258 in group B. Median TTS was 34 days. No association between clinical stage, nuclear grade, type of chemotherapy, type of surgery and TTS was detected. OS and RFS were significantly worse for group B compared with group A, with a hazard ratio of 3.1 (95% CI, 1.1–8.6 p = 0.03) and 3.1 (95% CI, 1.3–7.1 p = 0.008) respectively. Multivariate analysis confirmed that TTS was an independent prognostic factor in term of OS (p = 0.03) and RFS (p = 0.01). Even in the subgroup of patients with pCR, TTS continued to be an independent prognostic factor for both OS and RFS (p = 0.05 and p = 0.03). Conclusions: TTS after NST seems to influence survival outcomes. BC patients underwent surgery within 21 days experienced maximal benefit from previous treatment: this advantage is consistent and maintained over time.